The complexity of human infected AIV H5N6 isolated from China - Zhijie Zhang; Rui Li; Lufang Jiang; Chenglong Xiong; Yue Chen; Genming Zhao; Qingwu Jiang (BMC Infectious Diseases, 2016)
Abstract Background Novel avian influenza viruses (AIVs) of H7N9, H10N8, and H5N6 are currently circulating in China’s poultry flocks, occasionally infecting human and other mammals. Human infected AIV H5N6 in China during 2014–2015 is believed to be a triple reassortant originated from H6N6 and two clades of H5 viruses. The current report suggests that its reassortment history is more complicated. Methods Genomes of human infected isolates of AIV H5N6 were searched from the NCBI Influenza Virus Sequence Database and the Global Initiative on Sharing Avian Influenza Data. Sequences shared high identities with each segment of their genomes were obtained through the Basic Local Alignment Search Tool. Alignments were done by mafft-7.037-win32 program; 8 large-scale and then 8 gradually converged phylogenetic trees were constructed by using MEGA5.1/5.2/6.0 Software. Results The events that each segment of the genomes of human infected AIV H5N6 isolates circulated in China had evolved into its current status might have happened before 2013, and so were they then reassorted into the epidemic AIV H5N6. A/Guangzhou/39715/2014(H5N6) and A/Sichuan/26221/2014(H5N6) had their six internal segments (PB2, PB1, PA, NP, NEP, and M) in common, and were reassorted from AIVs H5N1 in the same period and same region as that of HA, while A/Yunnan/0127/2015(H5N6) derived its six internal segments from AIV H9N2 that has been prevalent in Eastern China since 2008. Conclusions AIV H5N6 isolates established from both human and poultry in China during 2014–2015 were heterogeneous; both AIVs H5N1 and H9N2 were involved in the reassortment of AIV H5N6 in China.